PENDUGAAN KOMPONEN RAGAM GENETIK PADA POPULASI TANAMAN JAGUNG HASIL SELEKS MASSA DENGAN INDEKS DASAR - I Wayan Sudika Sudika (Department of Agronomy Faculty of Agriculture University of Mataram and Indonesian Society of Agronomy Branch NTB, 2021)
This study aimed to determine the degree of additive variation and the dominant varietion of yield and fresh biomass and other properties and also to identify the narrow sense heritability of all observed traits. The research activity was carried out in two stages, namely making kinship with NC I and testing the results of the crosses. A total of 60 crosses were tested from 20 male parents. The design used for the crosses was a randomized block design with two replications. Each treatment (the result of crosses), planted in one row; each row contained 40 plants. The properties observed included plant height, number of leaves, fresh biomass weight, harvested dry ear weight, ear length, ear diameter, and yield. The data from the observations were analyzed by means of an analysis of variance with the model following the design of the NC I cross at the 5% ignificant level and continued with the estimation of the additive and dominant variants and the standard deviation of each of these variance evaluation. The results showed that the variety of additives was greater than the dominant variation, especially obtained in plant height, number of leaves, weight of fresh biomass per plant, ear length, and yield; on the other hand, the dry weight of harvested cobs and ear cobs had a smaller additive variety than the dominant variety. The heritability of narrow sense is high in fresh biomass weight and ear length; moderate on the number of leaves per plant, ear diameter, and yield; and classified as low on plant height and ear diameter. The increase in yield and fresh weight of the P8IS population should be carried out by further selection method.